Design and Development of Flow Loss Testing Device in Pipe Installation Using VDI 2221 Method - Ardian, Rifky Dwi; Fitri, Muhamad (Universitas Mercu Buana, 2025)
Piping installation is a medium for fluid transfer which has many design variations. The design used can affect the flow rate of the fluid. The effect comes from head losses which are divided into major losses and minor losses. Basically, major losses are losses caused by straight pipes while minor losses are losses due to pipe components. These components can be in the form of bends, connections, branching and changes in cross-sectional size. Losses that occur in pipe flow can be studied by direct simulation. To carry out a direct simulation, a test tool is needed that can help analyze losses that occur in fluid flow in pipe installations. The design that is carried out refers to the use of pipe installations that are often encountered including its components. The system design of the flow loss test equipment is selected using the VDI 2221 method. The selection of components is carried out by comparing the variations in the arrangement of system components. From the results of this comparison, the best variation was obtained with the results of the main PVC pipe, 108 bit Shimizu jet pump, ball valve type, pressure gauge capacity of 2.5 bar, flowmeter capacity of 1.5 m3/h, rotameter capacity of 2-20 GPM/10- 70 LPM. The tool has been completed built and tested so it is feasible to use.